Ginseng treatment improves psychomotor performance at rest and during graded exercise in young athletes - Ziemba, A. W.; Chmura, J.; Kaciuba-Uscilko, H.; Nazar, K.; Wisnik, P. (International Journal of Sport Nutrition and Exercise Metabolism, 1999)
This study was designed to determine the effect of ginseng treatment on multiple choice reaction time (RT) during exercise. Fifteen soccer players (age 19.07 ± 0.62 yrs) were placed in a double-blind manner into one of two groups: ginseng (n = 7), receiving 350 mg of ginseng daily for 6 weeks, or placebo (n = 8), receiving a placebo daily for 6 weeks. Before and after the treatment all the subjects performed an incremental bicycle ergometer exercise with intensity increasing 50 W every 3 min until volitional exhaustion. RT was measured before exercise, and then in the last 2 min of each exercise load. Maximal oxygen uptake (VO2max) and lactate threshold (LAT) were also determined from the exercise test. Ginseng treatment was found to shorten RT at rest and during exercise, shifting the exercise load associated with the shortest RT toward higher exercise loads. Neither ginseng nor placebo influenced VO2 max and LAT. In conclusion, ginseng extract does improve psychomotor performance during exercise without affecting exercise capacity.